POLA ASUH ORANGTUA AKAN MENINGKATKAN ADAPTASI SOSIAL ANAK PRASEKOLAH DI RA MUSLIMAT NU 202 ASSA’ADAH SUKOWATI BUNGAH GRESIK - Suana Suana; Firdaus Firdaus (Jurnal Ilmiah Kesehatan, 2014)
Each child has a different ability to adapt. Some children experience the late process of social adaptation during preschool age. Therefore, this research was purposed to find out the correlation between parenting pattern and social adaptation development in preschool children studying at RA Muslimat NU 202 Assa’adah Sukowati, Bungah, Gresik. The type of research was analytic done by applying cohort retrospective design. The population involved all parents and their children studying at the school mentioned above, totally 40 people, in which 36 respondents were taken as the samples by using probability sampling, namely simple random sampling technique. Questionnaires and observational sheets were used to collect the data, which were then analyzed by using Spearman’s Rank correlation test with the significance level of 0.05. The result of research showed that most of the respondents (55.6%) applied democrative, whereas nearly all of the children (80%) had a good social adaptation development. Moreover, the result of correlation test showed that p = (0.000) < α (0.05) so that H0 was rejected illustrating that there was a correlation between parenting pattern and social adaptation development in preschool children studying at RA Muslimat NU 202 Assa’adah Sukowati, Bungah, Gresik. The research concluded that the parents applying democratic parenting pattern resulted in a good social adaptation development in their children. Thus, they should apply the correct parenting pattern according to the age of their children.